Analysis of Fire Risk Factors with Methods Fishbone in Institute of Health Sciences Persada Husada Indonesia Building and Vocational School at SMK of Persada Husada Indonesia: Roshela, Herlina - Roshela, Roshela; Herlina, Herlina (Jurnal Persada Husada Indonesia, 2023)
Work Safety Act No. 1 of 1970 Chapter III Work Safety Requirements Article 3 paragraph 1 letter b and c stipulates that one of the requirements for production safety is preventing, reducing and extinguishing fires, as well as preventing and reducing the danger of explosions. This regulation is one of the basic requirements for risk control work against fire and explosion hazards. This research uses qualitative data with purposive sampling method. Data were obtained by direct observation, interviews and document review. To obtain valid data, data validation was carried out using the triangulation method. The focus of this research is K3 policy, planning, implementation, inspection and review related to fire control. The result of this research is Persada Husada Indonesia Institute Of Health Sciences and Persada Husada Indonesia Vocational School does not yet have an OSH policy. Planning regarding the fire risk assessment has not been carried out at the Persada Husada Indonesia Institute Of Health Sciences and Persada Husada Indonesia Vocational School. Implementation regarding fire control has not been maximized. Inspection and review regarding fire control has not been maximized. In the fire risk assessment, there are 3 types of fire risk hazards in the Persada Husada Indonesia Institute building and Persada Husada Indonesia Vocational School, that is, electrical cables that are not properly arranged with a value of 10 with an unacceptable risk, use of a portable terminal with a portable terminal with a value of 10 with an unacceptable risk acceptable, the amount of flammable material with a value of 5 with acceptable risk.